2021
DOI: 10.1038/s41598-021-92680-4
|View full text |Cite
|
Sign up to set email alerts
|

Linkage mapping and QTL analysis of flowering time in faba bean

Abstract: Flowering time marks the transition from vegetative to reproductive growth and is key for optimal yield in any crop. The molecular mechanisms controlling this trait have been extensively studied in model plants such as Arabidopsis thaliana and rice. While knowledge on the molecular regulation of this trait is rapidly increasing in sequenced galegoid legume crops, understanding in faba bean remains limited. Here we exploited translational genomics from model legume crops to identify and fine map QTLs linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 78 publications
1
25
0
Order By: Relevance
“…Interestingly, the region did not only have a large effect on the trait but is also highly conserved in multiple legumes, including Lotus japonicus (Gondo et al 2007 ), Medicago truncatula (Pierre et al 2008 ), chickpea (Cobos et al 2009 ), narrow-leafed lupin (Nelson et al 2006 ), and alfalfa (Robins et al 2007 ). The region on chromosome 5 from approximately 489 Mb to 602 Mb (comprising 244 genes) contains four of the peak markers identified for flowering time in this study, the QTL for flowering time identified from a bi-parental cross by Catt et al 2017 , as well as the peak markers identified in Cruz-Izquierdo et al ( 2012 ) and Aguilar-Benitez et al ( 2021 ). The region is syntenic to the region of Medicago truncatula chromosome 7 that harbors five flowering time genes and the spring1 locus (Yeoh et al 2013 ; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 64%
“…Interestingly, the region did not only have a large effect on the trait but is also highly conserved in multiple legumes, including Lotus japonicus (Gondo et al 2007 ), Medicago truncatula (Pierre et al 2008 ), chickpea (Cobos et al 2009 ), narrow-leafed lupin (Nelson et al 2006 ), and alfalfa (Robins et al 2007 ). The region on chromosome 5 from approximately 489 Mb to 602 Mb (comprising 244 genes) contains four of the peak markers identified for flowering time in this study, the QTL for flowering time identified from a bi-parental cross by Catt et al 2017 , as well as the peak markers identified in Cruz-Izquierdo et al ( 2012 ) and Aguilar-Benitez et al ( 2021 ). The region is syntenic to the region of Medicago truncatula chromosome 7 that harbors five flowering time genes and the spring1 locus (Yeoh et al 2013 ; Supplementary Fig.…”
Section: Discussionmentioning
confidence: 64%
“…In common bean, AM has been used for the identification of QTLs/gene(s) linked with iron, zinc, and protein contents [ 56 ]. Similarly, QTL mapping and the identification of marker–trait association have been carried out in faba bean for flowering time [ 57 ]. The marker–trait association has been identified for various traits in different legume crops, such as QTL for winter hardiness and leaf area in lentil [ 58 ], QTLs for number of branches and pods in soybean [ 59 ], QTL for resistance to ascochyta blight and early flowering in chickpea [ 60 ], and QTL for the determinacy gene ( Dt1 ) for determinant growth habit in pigeonpea [ 61 ].…”
Section: Development Of Genomic Resources In Legume Cropsmentioning
confidence: 99%
“…In faba bean Vicia faba , the candidate gene mapping and the quantitative trait loci (QTL) analysis revealed the cluster of FT loci close to the most conserved flowering time QTL on chromosome 5 in a region syntenic with a section of Medicago chromosome 7 containing FTa and FTc genes [ 58 ]. However, the authors failed to map individual FT genes within this region due to high sequence conservation [ 58 ].…”
Section: A Role Of the Legume Ft Genes In Vernaliz...mentioning
confidence: 99%